Pengaruh Pemahaman dan Pengetahuan, Sanksi, Serta Kebijakan Pajak terhadap Tingkat Kepatuhan Pajak Umkm pada Kota Bandung - Nantha Ardita Aulia Arifin; Siti Ardelia; Fadisya Azril Maharani; Ainun Nayla; Rizky Aulia Putri; Nuri Fujianti; Tengku Aurelia Putri Azhira (Yayasan Literasi Ilmiah Indonesia, 2026)
Purpose: The purpose of this research is to look at how well MSMEs understand and follow tax legislation, namely Article 21 of the Income Tax Code and Value Added Tax (VAT). The poor level of tax compliance among MSMEs is a driving force for this study. Many company owners still lack a good understanding of tax regulations and processes, which leads to less than ideal tax fulfillment. Method: The study takes a quantitative approach by surveying MSME players from different industries using questionnaires. To characterize the extent to which taxpayers understand taxes, the function of penalties for noncompliance, and the impact of tax policies on taxpayer compliance, descriptive and quantitative statistical methods were used to the gathered data. Finding: Most micro, small, and medium-sized enterprises (MSMEs) are aware of their tax responsibilities, but the findings show that they still have difficulty with tax calculation, reporting, and payment. Concerns over possible financial losses make tax penalties the most influential element on MSME tax compliance. Novelty: This study takes into account tax understanding and knowledge, tax sanctions, and tax policies as benchmarks for enhancing MSMEs’ tax compliance.